The Children's Blizzard, 1888 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Press, 2018)
When John Hale's parents moved from Chicago to a farm in the Dakota Territory in the late 1880s, he was not happy (too hot in summer, too cold in winter, and that is just the beginning); but after a year, and now eleven, he has settled in and made some friends at school--but when a sunny day in January 1888 turns abruptly into a deadly blizzard he will need all his strength and courage to survive what became known to history as The Children's Blizzard.
Includes bibliographical references.
Keywords: Blizzards -- Juvenile fiction -- History -- 19th century -- Dakota Territory; Pioneer children -- Juvenile fiction -- Dakota Territory; Survival -- Juvenile fiction -- Dakota Territory; Blizzards -- Fiction; Frontier and pioneer life -- Fiction -- Dakota Territory; Survival -- Fiction; Dakota Territory -- Juvenile fiction -- History; Dakota Territory -- Fiction